PERUBAHAN KONSENTRASI ALUMINIUM DAN SERAPAN FOSFOR OLEH TANAMAN PADA ULTISOL AKIBAT PEMBERIAN KOMPOS - Imam Wahyudi (Universitas Tribhuwana Tunggadewi, 2009)
A glasshouse experiment was conducted to judge the beneficial effects of Gliricidia sepium and Tithonia diversifolia composts on plant growth improvement, P availability and reduction of aluminium concentration in an Ultisol. Thirteen treatments consisting of two composts, six rates of each compost (5, 7.5, 10, 20, 40 and 80 t/ha) and one control (no added compost) were arranged in a randomized block design with three replicates. Each mixture of compost and soil was placed in a pot containing 8 kg of soil, and maize of Srikandi cultivar was grown on it for 45 days. At harvest, plant P content, soil pH, and soil aluminium concentration were measured. Results of this study showed that application of Gliricidia and Tithonia composts significantly reduced Alo concentration, increased Alp content, increased soil pH, increased P availability, and increased P taken up by maize grown for 45 days. The optimum rate of both Gliricidia and Tithonia composts should be 45 t/ha. However, at the same rate, optimum production gained by application of Tithonia compost would be higher than that of Gliricidia. This was due primary to the difference contents of humid acid and fulvic acid of the composts